ANALISIS STRATEGI PROMOSI TABUNGAN FAEDAH PT. BRI SYARIAH KC. BANJARMASIN - Nur Habibah; Ahmad Dakhoir (UIN Sunan Gunung Djati Bandung, 2020)
This study aims to describe and analyze using the SWOT method of promotion strategies carried out at PT. BRI Syariah KC Banjarmasin. The type of research used is field research with a qualitative approach. Then, the research data source is primary data that comes directly from the field. To obtain research data, data collection techniques by observation, interviews with MO (Operational Manager) FRO (Funding Relations Officer) and AO (Account Officer), and documentation. Then to analyze the data used analysis techniques of editing, categorization, and description. The results showed that the promotion strategy of Faedah savings carried out by BRI Syariah KC Banjarmasin which was carried out in the form of promotion when attacking the market, elementary school, junior high school, high school, company, college, collaborating with several companies and to prospective customers who want to make financing. Based on the SWOT analysis, BRI Syariah KC Banjarmasin still has many challenges and weaknesses that must be addressed so that the promotion is successful and helps to increase third party funds at BRI Syariah KC Banjarmasin.This study aims to describe and analyze using the SWOT method of promotion strategies carried out at PT. BRI Syariah KC Banjarmasin. The type of research used is field research with a qualitative approach. Then, the research data source is primary data that comes directly from the field. To obtain research data, data collection techniques by observation, interviews with MO (Operational Manager) FRO (Funding Relations Officer) and AO (Account Officer), and documentation. Then to analyze the data used analysis techniques of editing, categorization, and description. The results showed that the promotion strategy of Faedah savings carried out by BRI Syariah KC Bajarmasin which was carried out in the form of: promotion when attacking the market, elementary school, junior high school, high school, company, college, collaborating with several companies and to prospective customers who want to make financing. Based on the SWOT analysis, BRI Syariah KC Banjarmasin still has many challenges and weaknesses that must be addressed so that the promotion is successful and helps to increase third party funds at BRI Syariah KC Banjarmasin.